KNOWLEDGE AND UTILIZATION OF PAIN ASSESSMENT TOOLS AMONG SURGICAL NURSES AT FEDERAL MEDICAL CENTRE GUSAU, ZAMFARA STATE - Ismail, Tukur; Sulaiman, Tujjani; Tanko, Fatima; Yuguda, Najaatu; Arkilla, Bello (FUDMA Journal of Sciences, 2025)
Effective pain assessment is a cornerstone of quality patient care, especially in surgical settings where unmanaged pain can impede recovery and compromise outcomes. This study assessed the knowledge and utilization of pain assessment tools among surgical nurses at the Federal Medical Centre (FMC) Gusau, Zamfara State, Nigeria. Using a descriptive cross-sectional design and purposive sampling, 32 surgical nurses participated in a structured, self-administered questionnaire. Data were collected between October and November 2024, ensuring broad participation from nurses across all surgical units. Data analysis was conducted using Microsoft Excel, employing descriptive statistics such as frequencies, percentages, and charts to summarize key findings. Findings revealed that while 87.5% of nurses were aware of pain assessment tools, only a few were familiar with diverse tools beyond the Numeric Rating Scale (53.1%) and Visual Analogue Scale (31.3%). Approximately 62.5% had received formal training, and 56.3% reported using these tools every shift. However, significant barriers including difficulty interpreting results (81.3%), time constraints (75.0%), and inadequate training (62.5%) were identified. Respondents recommended increased training (87.5%) and enhanced institutional support as key interventions. The study concludes that, although awareness and self-reported confidence are relatively high, gaps in formal training, tool diversity, and institutional support hinder the effective assessment of pain. Strengthening nurse education and improving hospital policies are crucial to enhancing pain management outcomes in surgical care.